Participation of alien species in urban floras in different botanical and geographical zones of Ukraine: a preliminary assessment - Protopopova, Viera V.; Shevera, Myroslav V. (Biodiversity: Research and Conservation, 2008)
Results of a study on the participation of the group of alien species (kenophytes) in urban floras of different botanical and geographical zones of Ukraine are presented. The total list of kenophytes (497 species of vascular plants) is provided. The floristic composition, peculiarities of the taxonomic and geographical (according to the areas of origin) structures, and the degree of naturalization of kenophytes are analyzed. The results indicate a low floristic similarity between towns and cities. Climatic conditions play a more essential role in determining distribution patterns of kenophytes in urban areas in terms of the origin and the degree of naturalization parameters, whereas the taxonomic structure depends more on the area studied and economic development of a town/city.